ANALISIS KUALITAS WEBSITE SISTEM INFORMASI KINERJA PEGAWAI TERINTEGRASI (SIJAPATI) KUNINGAN MENGGUNAKAN METODE WebQual 4.0 DAN IMPORTANCE PERFORMANCE ANALYSIS (IPA) - Jannah, Syifa Raudhatul; Widodo, Suprih (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2026)
The development of digital transformation in government encourages the use of information systems to improve the effectiveness of civil servant performance management. The Government of Kuningan Regency developed the Integrated Employee Performance Information System (SIJAPATI) as a digital platform to support the management of Employee Performance Targets (SKP). However, the quality of the website and user satisfaction levels need to be evaluated to ensure the effectiveness of the system implementation. This study aims to analyze the quality of the SIJAPATI website and the level of user satisfaction based on the perceptions of civil servants (ASN). This research uses a quantitative approach by applying the WebQual 4.0 method, which consists of three main dimensions: usability, information quality, and service interaction quality, combined with Importance Performance Analysis (IPA) to determine system improvement priorities. Data were collected through questionnaires from 100 ASN respondents who use the SIJAPATI system. The data were analyzed using the WebQual Index (WQI), Customer Satisfaction Index (CSI), gap analysis, and IPA mapping. The results show that the quality of the SIJAPATI website is categorized as good to very good with a WQI value of 0.85, while the user satisfaction level is very high with a CSI value of 84.50%. However, the IPA analysis indicates that several attributes still require improvement priorities, particularly in system navigation, system professionalism, and transparency in performance evaluation mechanisms. These findings imply that improvements in navigation quality, system stability, and transparency of evaluation processes are necessary to enhance the SIJAPATI website service quality sustainably.   Keywords: WebQual 4.0; Importance–Performance Analysis; Customer Satisfaction Index; Website Quality; SIJAPATI.